Benturan Praktek Hukum Adat Baduy Terhadap Pendidikan Sebagai Elemen Dasar Hak Asasi Manusia - Syukur Destieli Gulo; Dian Ekawati (Program Studi Hukum Universitas Pamulang, 2020)
This study aims to explain the imbalance adatrecht of baduy, Lebak, Banten. This research uses the normative-empirical method with the category of Non Judicial Case Study, beginning with observation and interviews. The data collected was analyzed from a legal perspective and its implementation in the community, especially the adatrecht of baduy. The results of the study concluded that the prohibition of customary law on education has reduced and limited the use of the rights of Baduy tribesmen freely and responsibly. Education is a basic element of human rights which can have a very big influence on the welfare of a person's life, it is precisely limited and usurped by customary law which is an obstacle in realizing that welfare. Basically, the State provides protection, enforcement and fulfillment of Human Rights and cannot be reduced in its implementation.